JUMPA Vol.2 No.1 Feb 2015 PENGARUH KEPEMIMPINAN, MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DENGAN LOCUS OF CONTROL SEBAGAI VARIABEL MODERATING PADA PT. POS INDONESIA (PERSERO) MEDAN: PENGARUH KEPEMIMPINAN, MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DENGAN LOCUS OF CONTROL SEBAGAI VARIABEL MODERATING PADA PT. POS INDONESIA (PERSERO) MEDAN - Amdani Fakultas Ekonomi Universitas Persada Indonesia Y.A.I. Jakarta; Alex Zami Sekolah Tinggi Ilmu Ekonomi Y.A.I. Jakart (Jurnal Manajemen dan Perbankan (JUMPA), 2015)
This study aims to want to analyze the influence of leadership, motivation to work against the imployee performance with locus of control as variable a moderating on PT. Pos Indonesia (Persero) Medan branch office. Population in this study were those of employee of PT. Pos Indonesia (Persero), branch offices Medan as many as 346 people. Sample size the number is 78 people set with Slovin using formulas. Research method used is descriptive method and verifikatif with regression analysis and moderated regression analysis who seeks direct influence between three independent variables and one variable dependent. The results of data processing and analysis proven that: 1) Leadership influential on the performance of positive and significant with the value of 18,332 t count, 2) Locus Of Control positively and significant capable of moderating influence leadership against the employee performance groundless interaction test and test it with the difference in absolute value 3,194 t count, 3) Work motivation influential to the employee performance positive and significant with the value of 13,553 t count, 4) Locus Of Control positively and significant capable of moderating influence work motivation against the employee performance groundless interaction test and test it with the difference in absolute value 3,064 t count, 5) Leadership and work motivation of the influential together on the employee performnace of positive and significant with a value of count 242.223 F’.